Invasion genetics of Chromolaena odorata (Asteraceae): extremely low diversity across Asia - Yu, X.; He, Tianhua; Zhao, J.; Qiaoming, L. (Springer, 2014)
Chromolaena odorata is a native of America while a weed in many parts of tropical and subtropical regions in the world. Research into the invasion mechanisms of C. odorata contributes to a broader understanding of factors that facilitate plant adaptation, and also helps developing effective management strategies. In this study, we used three DNA fragments and six microsatellite loci: (1) to compare genetic diversity of C. odorata in its native and invaded regions; (2) to elucidate the invasive routes and identify possible source locations of C. odorata from America to Asia, with attempt to evaluate the possible mechanisms facilitating the successful invasion of this species. Despite two recorded independent introductions, DNA sequence data revealed only one single haplotype of C. odorata present throughout tropical Asia. All six microsatellite loci consistently exhibited extremely low genetic diversity in Asian populations compared to those from native ranges. Our results implied that there was likely only a single introduction to Asia, and Trinidad, Tobago and adjacent areas in the West Indies were the most likely source location of that introduction. The successful invasion of C. odorata in Asia may have been facilitated by the genotype with strong competitive ability.